PRIORITY PROGRAM APPROACH TO PARTNERSHIP LIQUIDATION BY INSTALLMENTS. - Simons, Harry (The Accounting Review, 1955)
Abstract In determining how cash is to be divided among partners, the conventional accounting approach is to regard any distributable cash as though it were the last to be made available to partners. This involves the assumptions that all remaining assets are worthless and will emerge as a complete loss, and, that any presently deficient partners or partners who may become deficient as a result of the loss of all remaining assets will be unable to meet their indebtedness to the firm, such deficiencies requiring absorption by remaining solvent partners. A schedule should be prepared which involves a recognition of partners' present equities and the portions of the equities that must be restricted to absorb the charges occasioned by a loss on remaining assets and the charges emerging from any capital deficiencies. The maximum loss that each partner can absorb in terms of his present respective equity in the firm must first be calculated. As cash is to become available, it should be applied in a manner that will bring the partners' equities ever closer to the point where they can absorb the same loss.